Cross-linguistic corpora for the study of translations: insights from the language pair English-German - Hansen-Schirra, Silvia; Neumann, Stella (Text, Translation, Computational Processing [TTCP], 2012)
This book is a contribution to the study of translation as a contact variety, and - more generally - to language comparison and language contact with a focus on English and German. Methodologically, the contributors implement an empirical research strategy with further applications in computational linguistics and language technology